Improvement in osteogenesis, vascularization, and corrosion resistance of titanium with silicon-nitride doped micro-arc oxidation coatings - Shen, Yiding; Fang, Kai; Xiang, Yun; Xu, Keyuan; Yu, Liang; Chen, Jiaquan; Ma, Pingping; Cai, Kaiyong; Shen, Xinkun; Liu, Jinsong (Frontiers in Bioengineering and Biotechnology, 2022)
Admittedly, titanium (Ti) implant has been widely used in treatment of tooth loss due to its excellent biocompatibility and mechanical properties. But how to improve its biological inert to increase osteointegration remains one of the most popular research topics. In the meanwhile, the continuous release of various metal ions in the oral microenvironment caused by fluid corrosion can also lead to implant failure. Therefore, it is urgent to simultaneously improve the bioactivity and corrosion resistance of Ti-based materials. In recent decades, micro arc oxidation (MAO) has developed into a surface modification technology to form a surface protective oxide layer and improve the comprehensive properties of Ti. In this study, nano silicon nitride (Si3N4) particles were doped into the surface of Ti by MAO treatment, which not only improved its corrosion resistance, but also endowed with excellent osteoinductive ability by enhancing alkaline phosphatase activity and osteogenic related gene expression. In addition, we also found that due to the presence of silicon, the Si3N4-doped materials showed excellent properties in angiogenesis, including promoting cell migration and tubule formation, which played an essential role in early recovery after implantation.